2022
DOI: 10.1039/d1ra05315a
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic docked covalent organic frameworks with high catalytic performance towards coupling/oxidation cascade reactions

Abstract: Cu(ii) and Pd(ii) ions were selectively coordinated within an imine-linked 2D COF that exhibited good catalytic performance towards a one-pot Suzuki coupling/oxidation cascade reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…However, the two peaks in the N1s spectrum shifted towards higher energy region which indicates that the Cr metal is co-ordinated to the MT-POF via CrÀ N bonds. [86] Appearance of weak signal at 407.7 eV can be attributed to the N1s of NO 3 À anion (Figure 6c, inset). [87,88] Successful metalation of MT-POF with Cr(III) can be ascertained from the peaks at 577 and 587 eV that correspond to the Cr 3 + 2p3/2 and Cr 3 + 2p1/2, respectively (Figure 6d).…”
Section: Characterizationmentioning
confidence: 98%
“…However, the two peaks in the N1s spectrum shifted towards higher energy region which indicates that the Cr metal is co-ordinated to the MT-POF via CrÀ N bonds. [86] Appearance of weak signal at 407.7 eV can be attributed to the N1s of NO 3 À anion (Figure 6c, inset). [87,88] Successful metalation of MT-POF with Cr(III) can be ascertained from the peaks at 577 and 587 eV that correspond to the Cr 3 + 2p3/2 and Cr 3 + 2p1/2, respectively (Figure 6d).…”
Section: Characterizationmentioning
confidence: 98%
“…Thereafter, the same group reported additional heterobimetallic Pd( ii )/Cu( ii )@TADP-COF which can catalyse a coupling–oxidation cascade reaction in water. 697…”
Section: Application Of Metalated Cofsmentioning
confidence: 99%
“…The yield of the C-S cleavage reaction was recorded up to 76%, and this was kept during five recycle tests (Figure 9c). Li et al [80] reported bimetallic porphyrin COFs that enabled a cascade reaction. The authors synthesized COFs by Schiff reaction of porphyrins with two different linear struts, resulting in M-COF composed of β-hydroxy imine and simple imine linkages.…”
Section: Catalytic M-cofs For Chemical Transformationsmentioning
confidence: 99%
“…Li et al. [ 80 ] reported bimetallic porphyrin COFs that enabled a cascade reaction. The authors synthesized COFs by Schiff reaction of porphyrins with two different linear struts, resulting in M‐COF composed of β‐hydroxy imine and simple imine linkages.…”
Section: Properties and Applicationsmentioning
confidence: 99%